Serum and Urine Biomarkers Can Predict Outcomes after Osteochondral Allograft Transplantation in the Knee - Cook, James L.; Stoker, Aaron M.; Rucinski, Kylee; Stannard, James P. (The Journal of Knee Surgery, 2025)
Osteochondral allograft transplantation (OCAT) is safe and effective for the treatment of large articular defects in the knee. Yet, there are no quantitative methods for predicting OCAT outcomes. This study was designed to analyze serum and urine biomarkers collected prior to OCAT to determine their capabilities for predicting outcomes with respect to functional graft survival. Prospectively collected data for patients undergoing primary multisurface knee OCAT, enrolled in an outcomes registry, were analyzed for graft survival. Blood and urine samples were collected prior to surgery for biomarker analyses. Biomarker concentrations were analyzed for the capability to predict OCAT failures (revision or arthroplasty) that occurred within the first 2 years. Fifty consecutive patients were included for analysis; the 2-year graft survival (success) rate was 80%. In samples obtained prior to OCAT, concentrations of serum hyaluronan (HA) and urine cross-linked C-telopeptide of type II collagen (CTX-II) were significantly higher for failure patients. A urinary biomarker panel containing cross-linked C-telopeptide of type I collagen (CTX-I), CTX-II, HA, IL-8, MMP-2, MMP-3, MMP-13, osteoprotegrin (OPG), and osteopontin (OPN) was able to predict the likelihood of treatment failure with an area under the curve (AUC) of 0.895, sensitivity of 85.3%, and specificity of 93.8%. Preoperative concentrations of urine CTX-II and urine MMP-3 were significantly associated with a higher risk for OCAT treatment failure. Serum and urine protein biomarkers analyzed prior to surgery have the potential to predict functional graft survival at 2 years following complex multisurface OCAT surgery in the knee. With further validation, these biomarkers may be useful as a component of the shared decision-making process for patients and health care teams to evaluate this treatment option. Level of Evidence 2, prospective cohort study.
Keywords: knee; osteochondral allograft transplantation; biomarkers; shared decision-making process; graft survival